Association between platelet distribution width and serum uric acid in Chinese population. (30th January 2019) - Liu, Xiaoxia; Wang, Huiying; Huang, Chao; Meng, Zhaowei; Zhang, Wenjuan; Li, Yongle; Yu, Xuefang; Du, Xin; Liu, Ming; Sun, Jinhong; Zhang, Qing; Gao, Ying; et al.
Abstract: Platelet distribution width (PDW) is a simple and inexpensive parameter, which could predict activation of coagulation efficiently. And it has been confirmed to have a significant role in many diseases. We aimed to explore the association between PDW and hyperuricemia in a large Chinese cohort. This cross‐sectional study recruited 61, 091 ostensible healthy participants (29, 259 males and 31, 832 females) after implementing exclusion criteria. Clinical data of the enrolled population included anthropometric measurements and serum parameters. Database was sorted by gender, and the association between PDW and hyperuricemia was analyzed after dividing PDW into quartiles. Crude and adjusted odds ratios of PDW for hyperuricemia with 95% confidence intervals were analyzed using binary logistic regression models. We found no significant difference in PDW values between the genders. Males showed significantly higher incidence of hyperuricemia than females. From binary logistic regression models, significant hyperuricemia risks only were demonstrated in PDW quartiles 2 and 3 in males ( P  < 0.05). This study displayed close association between PDW and hyperuricemia as a risk factor. It is meaningful to use PDW as a clinical risk predictor for hyperuricemia in males. © 2019 BioFactors, 45(3):326–334, 2019